Search for a Higgs boson decaying to weak boson pairs at LEP - Dova, María Teresa (2003)
A Higgs particle produced in association with a Z boson and decaying into weak boson pairs is searched for in 336.4 pb−1 of data collected by the L3 experiment at LEP at centre-of-mass energies from 200 to 209 GeV. Limits on the branching fraction of the Higgs boson decay into two weak bosons as a function of the Higgs mass are derived. These results are combined with the L3 search for a Higgs boson decaying to photon pairs. A Higgs produced with a Standard Model e+e− → Zh cross section and decaying only into electroweak boson pairs is excluded at 95% CL for a mass below 107 GeV.